Dynamic slicing of aspect-oriented software: an UML-based approach. (3rd July 2020) - Ray, Abhishek; Singh, Jagannath
In this paper, we propose a technique to compute the dynamic slice of UML models for aspect-oriented software. The UML architectural model for aspect-oriented software represents the 'core' components, 'aspectual' components and the relationship between them. Firstly, we construct aspect-oriented model dependence graph (AOMDG) as an intermediate representation of the UML model for aspect-oriented software. AOMDG is a combination of aspect-class dependence graph (ACDG) and aspect-sequence dependence graph (ASDG). ACDG is constructed by using a set of class and set of aspect class diagrams and ASDG is constructed by using a set of sequence and aspect sequence diagrams from the UML architectural model. Then, we propose an algorithm to compute the dynamic slice by traversing AOMDG by marking and unmarking the nodes for a particular scenario during run-time.